Determination of Anlotinib, a Tyrosine Kinase Inhibitor, in Rat Plasma by UHPLC-MS/MS and Its Application to a Pharmacokinetic Study - Zhe Wang; Le-jing Lian; Yan-yan Dong; Xiao Cui; Jian-chang Qian; Cheng-ke Huang; Rui-jie Chen; Wei Sun (Journal of Analytical Methods in Chemistry)
Anlotinib is a novel inhibitor of receptor kinase tyrosine with multitargets and has a broad spectrum of inhibitory action on tumor angiogenesis and growth. A simple and rapid UHPLC-MS/MS bioanalytical method was validated for the determination of anlotinib in rat plasma, using imatinib as an internal standard. An Acquity BEH C18 column was used to separate analytes. The eluents consisted of formic acid/water (0.1 : 100, v/v) and acetonitrile with a mobile phase. A triple quadrupole mass spectrometer was operated for the quantification with multiple reaction monitoring (MRM) to determine transitions: 408.2 ⟶ 339.1 for anlotinib, and 494.3 ⟶ 394.1 for imatinib. The validated range was 0.1–50 ng/mL for anlotinib. Mean recovery rate of anlotinib in plasma was ≥99.32% and reproducible. Also, the intra- and interday precisions were both below 15%. This robust method was successfully applied to support the pharmacokinetic study of anlotinib in rats.